Real-time driving cycle measurements of fuel consumption and pollutant emissions of a bi-fuel LPG-gasoline motorcycle - Vinh Nguyen Duy (Elsevier, 2021)
This paper conducted an experimental study on the performance and emission characteristics of bi-fuel gasoline-liquefied petroleum gas (LPG) for in-used fuel-injected motorcycles. By using an electric bi-fuel controller, the original engine can operate smoothly on either conventional fuel or alternative one. The performance was evaluated by comparing the brake power at the wheel of the test motorcycle with a different kind of fuel. The carbon balance method was used to determine the fuel consumption from instantaneous emission levels measured by the constant volume sampler system. The pollutant level was measured following the driving cycle test ECE R40. The exhaust emission of HC, CO, and NOx of the test vehicle fueled by LPG reduces 69.94%, 47.89%, and 46.48% compared to gasoline. The average fuel (kg/100 km) and energy (MJ/100 km) consumption were reduced by 14.78% and 12.84%, respectively. In contrast, average fuel consumption in l/100 km increased by 11.10%. The degradation in engine performance was observed. The best brake power at the wheel was reduced by 19.42% on average. The developed bi-fuel system could be a feasible solution for environmental protection, fuel economy and guarantee the long life of currently used motorcycles in Vietnam’s current context.